2011
DOI: 10.1371/journal.pone.0028710
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin Regulates Lamellipodia Formation by Assembling a Protein Complex That Includes Ship2, Filamin and Lamellipodin

Abstract: Actin dynamics has emerged at the forefront of podocyte biology. Slit diaphragm junctional adhesion protein Nephrin is necessary for development of the podocyte morphology and transduces phosphorylation-dependent signals that regulate cytoskeletal dynamics. The present study extends our understanding of Nephrin function by showing in cultured podocytes that Nephrin activation induced actin dynamics is necessary for lamellipodia formation. Upon activation Nephrin recruits and regulates a protein complex that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 61 publications
0
38
0
1
Order By: Relevance
“…This suggests that the presence of the SHIP2-Myo1c complex might be rather specific for N1 cells. Interestingly, in a different cell type, nephrin regulates lamellipodia formation by assembling a protein complex that includes SHIP2, filamin and lamellipodin (Venkatareddy et al, 2011). SHIP2 is part of the adhesome, and it has been proposed that, on average, each adhesome protein has approximately nine different potential partners (Zaidel-Bar and Geiger, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the presence of the SHIP2-Myo1c complex might be rather specific for N1 cells. Interestingly, in a different cell type, nephrin regulates lamellipodia formation by assembling a protein complex that includes SHIP2, filamin and lamellipodin (Venkatareddy et al, 2011). SHIP2 is part of the adhesome, and it has been proposed that, on average, each adhesome protein has approximately nine different potential partners (Zaidel-Bar and Geiger, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…50 The previously described tyrosin phosphorylation site on nephrin was not detected, which may either be the result of the not optimal access of trypsin to this site or due to a low baseline phosphorylation because several studies have shown that nephrin tyrosine phosphorylation is inducible upon ligation of the extracellular domain. [51][52][53] We focused on studying phosphorylation of the PHB domain protein podocin. Mutations in the podocin gene (NPHS2) are a major cause of steroid-resistant nephrotic syndrome in children.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrin's ability to regulate actin dynamics in a phosphorylation-dependent manner has been demonstrated by us and other investigators (2)(3)(4)(5)(6). A critical role for nephrin is suggested by the lack of normal foot process development in mice lacking nephrin or humans born with nephrin mutations (7,8).…”
mentioning
confidence: 83%
“…In vitro studies have shown that engagement of the nephrin extracellular domain results in Src family kinase Fyn-dependent tyrosine phosphorylation of the nephrin cytoplasmic domain (6,9,10). Phosphorylated nephrin then recruits the Src homology 2 (sh2) domain-containing proteins Nck1/Nck2, the p85 subunit of phosphatidylinositol 3-kinase (PI3K), and Crk (3)(4)(5)(6)11) and other components of the actin polymerization complex (2,3,5,12,13). Mice with the Src family kinase Fyn deleted develop proteinuria and foot process defects that are evident at 7 weeks of age (10,14).…”
mentioning
confidence: 99%